Establishment and Culture of Human Intestinal Organoids Derived from Adult Stem Cells. (17th September 2020) - Pleguezuelos‐Manzano, Cayetano; Puschhof, Jens; van den Brink, Stieneke; Geurts, Veerle; Beumer, Joep; Clevers, Hans
Abstract: Human intestinal organoids derived from adult stem cells are miniature ex vivo versions of the human intestinal epithelium. Intestinal organoids are useful tools for the study of intestinal physiology as well as many disease conditions. These organoids present numerous advantages compared to immortalized cell lines, but working with them requires dedicated techniques. The protocols described in this article provide a basic guide to establishment and maintenance of human intestinal organoids derived from small intestine and colon biopsies. Additionally, this article provides an overview of several downstream applications of human intestinal organoids. © 2020 The Authors. Basic Protocol 1 : Establishment of human small intestine and colon organoid cultures from fresh biopsies Basic Protocol 2 : Mechanical splitting, passage, and expansion of human intestinal organoids Alternate Protocol : Differentiation of human intestinal organoids Basic Protocol 3 : Cryopreservation and thawing of human intestinal organoids Basic Protocol 4 : Immunofluorescence staining of human intestinal organoids Basic Protocol 5 : Generation of single‐cell clonal intestinal organoid cultures Support Protocol 1 : Production of Wnt3A conditioned medium Support Protocol 2 : Production of Rspo1 conditioned medium Support Protocol 3 : Extraction of RNA from intestinal organoid cultures